2013
DOI: 10.1163/15707563-00002407
|View full text |Cite
|
Sign up to set email alerts
|

Body shape evolution of Chromis and Azurina species (Percifomes, Pomacentridae) of the eastern Pacific

Abstract: Chromis is a circumglobal tropical and temperate genus with over 84 species of damselfishes. Studies based in osteological and molecular data have cited the relationship between Azurina and Chromis in the eastern Pacific. The main objectives of the study are: (1) to characterize size and shape in all Chromis and Azurina species of the eastern Pacific, (2) explore the phylogenetic signal of external morphology, and (3) present a hypothesis of the diversification process of this group. According to the results, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…1 ) is a major morphological trend across teleost species [3] [5] . Studies on overall body shape or shape of part of the body (often part of the cranium), have found that elongation is the principal axis of shape diversity within clades of Pomacentridae [7] [10] , Balistidae [11] , Cichlidae [12] , Anguilliformes [13] , [14] and Labridae [15] . A major role for elongation has even been described several times intraspecifically (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) is a major morphological trend across teleost species [3] [5] . Studies on overall body shape or shape of part of the body (often part of the cranium), have found that elongation is the principal axis of shape diversity within clades of Pomacentridae [7] [10] , Balistidae [11] , Cichlidae [12] , Anguilliformes [13] , [14] and Labridae [15] . A major role for elongation has even been described several times intraspecifically (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The largest source of morphological variation observed in the damselfish locomotor system was related to the rostro‐caudal elongation of the fish body, a major trend in shape diversity in reef fishes (Ward and Mehta, ; Aguilar‐Medrano et al, ; Aguilar‐Medrano, ; Claverie and Wainwright, ). Although, it is interesting to note that the three studied ecological variables do not show significant relationships with the first axis of variation but instead with the secondary axes.…”
Section: Discussionmentioning
confidence: 99%
“…While the ecological variables studied in our analysis are highly related to locomotion, they also influence feeding behavior. For example, deep‐bodies species with short caudal peduncles were typically associated with slower, more maneuverable swimmers (Bartol et al, ; Fulton, ; Aguilar‐Medrano, ). In turn, these characteristics were associated with being territorial and herbivorous (Frédérich et al, ; Cooper and Westneat, ; Aguilar‐Medrano et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among damselfish species, there is a strong relationship between habitat use, feeding, behavior, and morphology (Emery 1973;Fulton 2007;Frédérich et al 2008Frédérich et al , 2013Aguilar-Medrano 2013Aguilar-Medrano et al 2011, 2016. The ecological conditions that each species are exposed to since their separation by the Isthmus of Panama may have shaped their niche and morphology over time.…”
Section: Introductionmentioning
confidence: 99%